2021
DOI: 10.3389/fphar.2020.575294
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Scutellaria baicalensis Georgi and Sophora japonica L. ameliorate Renal Function by Regulating Gut Microbiota in Spontaneously Hypertensive Rats

Abstract: Chronic kidney disease (CKD) is becoming a notable health concern globally. The combination of Scutellaria baicalensis Georgi (SB) and Sophora japonica L. (SJ) has been demonstrated to have anti-hypertensive effects and improve kidney injury clinically. This study aimed to explore the renal protective effect of the combination of SB and SJ against CKD and clarify the potential mechanisms. Male spontaneously hypertensive rats (SHR) were used to induce hypertensive nephropathy and were treated with SB or SJ sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…As a specific intestinal growth factor, GLP-2 can promote the growth of normal intestinal mucosa, repair the damaged intestinal epithelium and protect the intestinal mucosal barrier ( Brubaker, 2018 ; Chang et al, 2021 ). Moreover, SCFAs, especially butyrate, can enhance the β-oxidation process of the cells in the intestinal mucosa, consume oxygen in the intestinal lumen and then create a favourable intestinal microenvironment to promote the growth of beneficial bacteria and inhibit the proliferation of potential pathogenic microorganisms; ultimately, the immune inflammatory response related to hypertension is alleviated, and target organ damage is relieved ( Cani, 2017 ; Guan et al, 2020 ). Similarly, Kim et al confirmed that butyrate treatment in mice with Ang II-induced hypertension can ameliorate microbial imbalance and intestinal barrier dysfunction, thereby reducing the mean arterial pressure ( Kim et al, 2018 ).…”
Section: Possible Mechanism Of Scfas Regulating Blood Pressurementioning
confidence: 99%
“…As a specific intestinal growth factor, GLP-2 can promote the growth of normal intestinal mucosa, repair the damaged intestinal epithelium and protect the intestinal mucosal barrier ( Brubaker, 2018 ; Chang et al, 2021 ). Moreover, SCFAs, especially butyrate, can enhance the β-oxidation process of the cells in the intestinal mucosa, consume oxygen in the intestinal lumen and then create a favourable intestinal microenvironment to promote the growth of beneficial bacteria and inhibit the proliferation of potential pathogenic microorganisms; ultimately, the immune inflammatory response related to hypertension is alleviated, and target organ damage is relieved ( Cani, 2017 ; Guan et al, 2020 ). Similarly, Kim et al confirmed that butyrate treatment in mice with Ang II-induced hypertension can ameliorate microbial imbalance and intestinal barrier dysfunction, thereby reducing the mean arterial pressure ( Kim et al, 2018 ).…”
Section: Possible Mechanism Of Scfas Regulating Blood Pressurementioning
confidence: 99%
“…( Aanouz et al, 2021 , Choi et al, 2014 , Citroner, 2020 , Davis and Kuttan, 2000 , Diao et al, 2021 , Gabbas et al, 2019 , El-Nabarawy et al, 2019 , Enmozhi et al, 2021 , Fraissé et al, 2020 , Fraissé et al, 2020 , Ge et al, 2013 , Anandhan et al, 2013 , Geng et al, 2020 , Gidwani and Alaspure, 2010 , Guan et al, 2021 , Gupta et al, 2021b , Gupta and Singh, 2014 , Gyebi et al, 2021 , Han et al, 2006 , Harun et al, 2015 , Hékimian et al, 2021 , Anonymous 2020b , Hékimian et al, 2020 , Interdisciplinary committee for integration of ayurveda and yoga interventions in the 'National clinical management protocol: COVID-19′ 2020 , Javed et al, 2011 , Jiang et al, 2017 , Jin et al, 2020 , Jordan et al, 2018 , Definition Task Force et al, 2012 , Khan and Al-Balushi, 2021 , Khotimah et al, 2015 , Khotimah et al, 2015 , Ashraf, 2018 , Assiri et al, 2013 , Kumaki et al, 2011 , Kupeli et al, 2007 , Latha et al, 2000 , Lau et al, 2008 , Atay Balkan et al, 2018 , Lee et al, 2017 , Lee et al, 2018 , Lee et al, 2017 , Lee et al, 2011 , Lee et al, 2021 , Li and De Clercq, 2020 , Li and Yu, 2006 , Li et al, 2020 , Avoseh et al, 2020 , Li et al, 2003 , Li et al, 2016 , Li et al, 2020 , Lim et al, 2020 , Limanaqi et al, 2020 , Liu et al, 2020 , …”
Section: Uncited Referencesmentioning
confidence: 99%
“…78 Furthermore, SCFAs, particularly butyrate, can alleviate immune inflammatory response and organ damage through enhancing the βoxidation process of cells in the intestinal mucosa and consuming oxygen in the intestinal lumen and then creating a favourable intestinal microenvironment that promotes the proliferation of beneficial bacteria while inhibiting the growth of potentially pathogenic micro-organisms. 80 SCFAs participate in CVD occurrence and development through several pathways; however, most of the studies on SCFAs are phenotypic descriptions, and the specific molecular mechanisms remain unexplained. Further studies are needed to elucidate the potential effects and internal mechanisms of SCFAs on CVD, which could provide fundamental information for the prevention and treatment of CVD.…”
Section: Scfasmentioning
confidence: 99%
“…Besides, after binding to GPR109A, butyrate can promote anti‐inflammatory properties in colonic macrophages and dendritic cells, leading to differentiation of Tregs and IL‐10‐producing T cells 78 . Furthermore, SCFAs, particularly butyrate, can alleviate immune inflammatory response and organ damage through enhancing the β‐oxidation process of cells in the intestinal mucosa and consuming oxygen in the intestinal lumen and then creating a favourable intestinal microenvironment that promotes the proliferation of beneficial bacteria while inhibiting the growth of potentially pathogenic micro‐organisms 80 . SCFAs participate in CVD occurrence and development through several pathways; however, most of the studies on SCFAs are phenotypic descriptions, and the specific molecular mechanisms remain unexplained.…”
Section: The Impacts Of Gm On the Immunopathology Of Atherosclerosismentioning
confidence: 99%